Zinc in infertility and infection (2002)
Seminal zinc may be associated with seminal and prostatic function. The role of zinc in genital tract infection and infertility is controversial. The study was undertaken to elucidate the role of zinc in infertility and infection in order to explain the increasing rise in male infertility. Eighty-three adult males aged 18-56 years participated in the study. 25 were fertile, 45 were infertile while 15 had sexually transmitted diseases (STDs). Zinc was estimated by atomic absorption spectrophotometry. Students t-test and ANOVA- one way were used for analysis of data. Seminal zinc values were not significantly different between groups tested and within the infertile groups (p > 0.05). It is suggested that seminal zinc may have little or no contribution to infection and infertility.